ChemInform Abstract: Fast, Solvent‐Free Asymmetric Alkynylation of Prochiral sp3 C—H Bonds in a Ball Mill for the Preparation of Optically Active Tetrahydroisoquinoline Derivatives. Issue 29 (1st July 2013) - Yu, Jingbo; Li, Zhenhua; Jia, Kanyan; Jiang, Zhijiang; Liu, Menglu; Su, Weike
Abstract: The asymmetric cross‐dehydrogenative coupling between tetrahydroisoquinolines and terminal alkynes is performed in a ball mill (2 copper balls) with silica gel as grinding agent.